The Prefix Ta-: From Kambera to Indonesian - Raynesta Mikaela Indri Malo (Journal of Language and Literature, 2023)
This research explores the borrowing of prefix ta- from bahasa Kambera (BK) to bahasa Indonesia (BI). This study is exceptional since the borrowing is from the non-dominant (as donor) language to the dominant language (as recipient) which has never existed before (there is no data of words borrowed from BK to BI). Besides, most borrowing from local languages in Indonesia to BI are in forms of words, not affixes. This descriptive qualitative study finds that, as its function in BK, the prefix ta- also has the same role in BI. It is used to derive the agentless intransitive achievement verbs with no agent. The prefix ta- is attached directly to the roots. The roots mostly are transitive and intransitive verbs, as well as adjectives and the derived forms after ta- is attached are mostly intransitive verbs and limited adjective (used as modifier in noun phrase). The prefix ta- is borrowed through direct borrowing which rely on the knowledge of the speakers. The borrowing occurred in the past when native speaker of Kambera were insisted on using bahasa Indonesia as the formal language. The practical use of the prefix ta- could be the most prominent reason of why this phenomenon happened.